Aberrations of DNA Repair Pathways in Prostate Cancer: Future Implications for Clinical Practice? - Caffo, Orazio; Veccia, Antonello; Kinspergher, Stefania; Rizzo, Mimma; Maines, Francesca (Frontiers in Cell and Developmental Biology, 2018)
Patients who are carriers of inherited mutations in essential component of DNA repair pathways have a significantly higher lifetime risk for developing cancer compared to the population of reference. Recent advances in DNA next-generation sequencing technology have allowed screening for carriers of those mutations, allowing development of promising risk-reduction strategies and providing the rationale to personalize the therapeutic approach for these patients. New intriguing scenarios are opening nowadays for the management of prostate cancer in patients with germline or somatic mutations in components of DNA repair pathways (e.g. BRCA1 and BRCA2 genes), such as specific screening policies and new therapeutic strategies involving PARP inhibitors or platinum-based chemotherapy.